PENGARUH FREE CASH FLOW, LEVERAGE, PROFITABILITAS DAN SALES GROWTH TERHADAP MANAJEMEN LABA - Basir, Shiera Indira; Muslih, Muhamad (Aksara Public, 2019)
The purpose of this study is to analyze what factors can affect the company in earning management. This study intends to determine the effecy of independent variabels both simultaneously and passively. In this study, independent variabels were used, namely free cash flow, leverage, profitability and sales growth to earning management. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange during the period 2013-2017. The sample in this study was determined using a purposive sampling technique so that 7 companies for 5 years. The analysis technique used in this study is panel data regression analysis using the Eviews 10.0 application. Based on this result of research showed that free cash flow, leverage, profitability and sales growth has significant simultaneously on earning management. While, partially profitability has a significant effect on the positive direction on earning management and free cash flow, leverage and sales growth have no significant effect on the negative direction on earning management.